Catalyst for producing graphite nanofibers and carbon monoxide-free hydrogen
By using a catalyst composition composed of specific elements to catalyze the decomposition of methane, the problems of easy aggregation of catalyst particles and reduced activity in existing technologies are solved, achieving the effect of efficient preparation of high-purity carbon nanostructures and hydrogen, which is suitable for commercial-scale production.
Patent Information
- Application Number
- CN202280052404.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-26
- Filing Date
- 2022-07-26
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-07-26
AI Technical Summary
Existing catalysts are difficult to efficiently catalyze the decomposition of methane into high-quality carbon nanostructures and hydrogen on a commercial scale, and the catalyst particles are prone to aggregation, which leads to a decrease in activity, making it difficult to achieve the control and commercial application of high-purity carbon nanomaterials.
The catalyst composition is represented by the chemical formula αwNixβyO or αwNixβyγzO, where α, β, and γ are specific elements. By controlling the metallic state and proportion of nickel in the catalyst composition, combined with calcination and reduction processes, a catalyst capable of efficiently catalyzing the decomposition of methane into graphite nanofibers and carbon monoxide-free hydrogen at lower temperatures can be prepared.
This method enables efficient catalytic decomposition of methane at lower temperatures, producing high-purity graphite nanofibers and carbon monoxide-free hydrogen. It improves the stability and activity of the catalyst, reduces operating costs, and is suitable for commercial-scale production.
Smart Images

Figure BDA0004682407370000131 
Figure BDA0004682407370000141
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority to U.S. Provisional Patent Application 63 / 225,733, filed July 26, 2021, the entire contents of which are incorporated herein by reference. Technical Field
[0003] This disclosure relates to catalyst compositions for the commercial-scale catalytic decomposition of methane to produce solid carbon products and hydrogen, and methods for manufacturing and using such catalyst compositions. Background Technology
[0004] According to the following reaction scheme (1), the thermal decomposition of methane into carbon and hydrogen is a moderately endothermic process, but the energy requirement for each mole of carbon produced (75.6 kJ / mol C) is far lower than that required by the steam methane reforming (SMR) process (approximately 190 kJ / mol C). Therefore, although the SMR process theoretically produces twice as many moles of hydrogen per mole of methane (four moles) as thermal decomposition (two moles), the energy required for this process is disproportionately higher (thermal decomposition produces 37.8 kJ / mol H2, while SMR produces approximately 47.5 kJ / mol H2). Furthermore, due to impurities and reaction byproducts, the SMR process typically produces only about 3.5 moles of H2 per mole of methane, further increasing the energy requirement to approximately 54.3 kJ / mol H2. In addition, unlike the SMR process, hydrogen produced by the thermal decomposition of methane can be prepared in an anaerobic environment without the water-gas shift reaction, thus allowing the production of high-purity carbon and a hydrogen stream free of carbon monoxide.
[0005] CH4(g) + 75.6 kJ / mol → C (s) + 2 H2 (g) (1)
[0006] For a long time, the thermal decomposition of natural gas has been used to produce carbon black, with the resulting hydrogen serving as a supplemental fuel for the process. These processes are typically carried out in a semi-continuous manner using two reactors in series at high operating temperatures (typically around 1,400 °C), but those skilled in the art have attempted to reduce these operating temperatures through catalysis. Data on the catalytic decomposition of methane using cobalt-based, chromium-based, iron-based, nickel-based, platinum-based, palladium-based, and rhodium-based catalysts have been reported in the literature; see, for example, Marina A. Ermakova et al., “Decomposition of methane over iron catalysts at the range of moderate temperatures: the influence of structure of the catalytic systems and the reaction conditions on the yield of carbon and morphology of carbonfilaments,” 201(2) Journal of Catalysis 183 (July 2001), the entire contents of which are incorporated herein by reference.
[0007] Compared to thermal decomposition, direct catalytic decomposition of methane offers two major advantages: (i) the operating temperature can be significantly reduced, from about 1,400 °C to at least as low as about 550 °C (typically between about 550 °C and about 725 °C), thus significantly reducing the energy input requirements of the process; and (ii) by using carefully selected catalysts, a variety of high-value engineered carbon nanostructures can also be prepared, thereby increasing the commercial value of the process. Since natural gas is widely and abundantly available, the industrial-scale catalytic decomposition of methane to produce hydrogen and high-value carbon nanostructures is technically feasible. However, for this decomposition process to be practically (i.e., commercially and economically) meaningful, highly efficient catalysts that have not yet been available are required. These catalysts should exhibit high activity over a long period and continue to function even in the presence of high concentrations of accumulated carbon.
[0008] Furthermore, the catalytic decomposition of methane can be a erratic process due to the stringent requirements on metal particle size and the tendency of reaction conditions to adversely affect catalyst morphology. Previous work has shown that the yield of solid carbon is highest when the average particle size of the catalyst is about 30 to 40 nm, but nickel catalyst particles may undergo undesirable aggregation as soon as the catalyst comes into contact with methane; for example, see MAErmakova et al., “XRD studies of evolution of catalytic nickel nanoparticles during synthesis of filamentous carbon from methane,” 62(2) Catalysis Letters 93 (Oct. 1999), the entire contents of which are incorporated herein by reference. This particle sintering behavior leads to a reduction in catalytic activity, but it is very difficult or impossible to operate the catalytic methane decomposition process on a commercial scale using particles as small as 30 to 40 nm; for practical application in industrial settings, catalyst particles need to be at least an order of magnitude larger.
[0009] Therefore, while the concept of producing carbon and hydrogen through the catalytic decomposition of methane has attracted considerable interest and demonstrated technical feasibility, it remains challenging to achieve the sustained commercial-scale production of the desired high-quality carbon-containing products. In particular, in addition to the catalyst particle size limitations discussed above, many prior methods in the art have failed to provide any degree of control over the type of carbon nanomaterials produced. Consequently, the carbon-containing products of these methods must be purified through typically difficult, expensive, and / or time-consuming chemical and physical processes, making them impractical for commercial applications. For example, while the preparation of carbon nanofibers using NiMgO and NiMgCuO catalysts is well-known in the art (e.g., see U.S. Patents 6,995,115 and 7,001,586 to Wang et al., the entire contents of which are incorporated herein by reference), these catalysts produce unstable mixtures of nanomaterials with amorphous carbon powder; the former is difficult to separate / purify, and the latter has very limited commercial value.
[0010] Therefore, there is a need in the art for catalyst compositions for methane decomposition processes that can improve the performance of these processes by enabling the preparation of selected carbon nanomaterials of high quality and / or high purity. Summary of the Invention
[0011] In one aspect of this disclosure, the catalyst composition comprises the general chemical formula α w Ni x β yO represents the element selected from the group consisting of boron (B), aluminum (Al), gallium (Ga), indium (In), thallium (Tl), and combinations thereof, β is selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and combinations thereof, the x:y ratio is at least about 1.0 and not more than about 6.2, and at least about 25% of the active nickel sites in the catalyst composition are in a metallic state.
[0012] In the embodiments, α can be aluminum (Al).
[0013] In the embodiments, β may be magnesium (Mg).
[0014] In the embodiments, the w:x ratio may be at least about 0.1 and no more than about 0.5.
[0015] In the embodiments, the x:y ratio may be at least about 1.8 and no more than about 2.8.
[0016] In the examples, at least about 50% of the active nickel sites in the catalyst composition may be in a metallic state.
[0017] In another aspect of this disclosure, the catalyst composition comprises the general chemical formula α w Ni x β y γ z O represents the catalyst composition, wherein α is at least one element selected from the group consisting of boron (B), aluminum (Al), gallium (Ga), indium (In), thallium (Tl), and combinations thereof; β is at least one element selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and combinations thereof; γ is at least one element selected from the group consisting of copper (Cu), silver (Ag), gold (Au), and combinations thereof; the x:y ratio is at least about 1.3 and not more than about 3.6; the x:z ratio is at least about 1.0 and not more than about 19.0; and at least about 25% of the active nickel sites in the catalyst composition are in a metallic state.
[0018] In the embodiments, α can be aluminum (Al).
[0019] In the embodiments, β may be magnesium (Mg).
[0020] In an embodiment, γ can be copper (Cu).
[0021] In the embodiments, the w:x ratio may be at least about 0.1 and no more than about 0.5.
[0022] In the embodiments, the x:y ratio may be at least about 1.8 and no more than about 2.8.
[0023] In the embodiments, the x:z ratio may be at least about 2.3 and not more than about 9.0.
[0024] In the examples, at least about 50% of the active nickel sites in the catalyst composition may be in a metallic state.
[0025] In the embodiments, at least about 25% of the active sites of one or more γ elements in the catalyst composition may be in a metallic state. At least about 50% of the active sites of one or more γ elements in the catalyst composition may, but not necessarily, be in a metallic state.
[0026] In another aspect of this disclosure, a method for manufacturing a catalyst composition includes: (a) providing a catalyst precursor composition comprising w parts by molar amount of one or more α elements, x parts by molar amount of nickel, and y parts by molar amount of one or more β elements, wherein the one or more α elements are selected from the group consisting of boron (B), aluminum (Al), gallium (Ga), indium (In), and thallium (Tl); the one or more β elements are selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); and the x:y ratio is at least about 1.0 and not more than about 6.2; (b) calcining the catalyst precursor composition at a temperature of at least about 500°C and not more than about 1,000°C to form a calcine product; and (c) reducing the calcine product at a temperature of at least about 600°C and not more than about 1,000°C in an atmosphere containing hydrogen to form the catalyst composition.
[0027] In the embodiments, one or more α elements may comprise aluminum (Al) or be composed of aluminum (Al).
[0028] In the embodiments, one or more β elements may comprise or consist of magnesium (Mg).
[0029] In the embodiments, the w:x ratio may be at least about 0.1 and no more than about 0.5.
[0030] In the embodiments, the x:y ratio may be at least about 1.8 and no more than about 2.8.
[0031] In the embodiments, after step (c), at least about 50% of the active nickel sites in the catalyst composition may be in a metallic state.
[0032] In the embodiments, the catalyst precursor composition may further comprise one or more γ elements in parts by molar, wherein the one or more γ elements are selected from the group consisting of copper (Cu), silver (Ag) and gold (Au); the x:y ratio is at least about 1.3 and not more than about 3.6; and the x:z ratio is at least about 1.0 and not more than about 19.0.
[0033] In the embodiments, one or more γ elements may comprise or consist of copper (Cu).
[0034] In the embodiments, the x:z ratio may be at least about 2.3 and not more than about 9.0.
[0035] In the embodiments, after step (c), at least about 25% of the active sites of one or more γ elements in the catalyst composition may be in a metallic state. After step (c), at least about 50% of the active sites of one or more γ elements in the catalyst composition may, but do not need to, be in a metallic state.
[0036] In this embodiment, the temperature in step (b) can be at least about 600°C and not more than about 900°C. The temperature in step (b) can, but does not need to be, at least about 750°C and not more than about 850°C.
[0037] In an embodiment, the atmosphere in step (c) may also contain argon.
[0038] In an embodiment, the temperature in step (c) can be at least about 850°C and not more than about 950°C.
[0039] In another aspect of this disclosure, a method for catalytically decomposing methane to prepare elemental carbon solid and a product stream containing hydrogen includes (a) providing a product stream of general chemical formula α w Ni x β y O or α w Ni x β y γ z The catalyst composition represented by O, wherein α is at least one element selected from the group consisting of boron (B), aluminum (Al), gallium (Ga), indium (In), thallium (Tl) and combinations thereof, β is at least one element selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba) and combinations thereof, γ is at least one element selected from the group consisting of copper (Cu), silver (Ag), gold (Au) and combinations thereof, the x:y ratio is at least about 1.0 and not more than about 6.2, and when γ is present, the x:z ratio is at least about 1.0 and not more than about 19.0, and at least about 25% of the active nickel sites in the catalyst composition are in a metallic state; and (b) the catalyst composition is contacted with a reactant gas stream containing methane gas at a temperature of at least about 500°C and not more than about 800°C.
[0040] In the embodiments, α can be aluminum (Al).
[0041] In the embodiments, β may be magnesium (Mg).
[0042] In an embodiment, γ can be copper (Cu).
[0043] In the embodiments, the w:x ratio may be at least about 0.1 and no more than about 0.5.
[0044] In the embodiments, the x:y ratio may be at least about 1.8 and no more than about 2.8.
[0045] In an embodiment, when γ is present, the x:z ratio can be at least about 2.3 and no more than about 9.0.
[0046] In the examples, at least about 50% of the active nickel sites in the catalyst composition may be in a metallic state.
[0047] In the embodiments, at least about 25% of the active sites of one or more γ elements in the catalyst composition are in a metallic state. At least about 50% of the active sites of one or more γ elements in the catalyst composition may, but need not, be in a metallic state.
[0048] In an embodiment, at least about 85% of the carbon solids by weight can be formed as graphite nanofibers, which include platelets aligned perpendicularly to the fiber axis.
[0049] In the embodiments, the product stream may be free of carbon monoxide.
[0050] In an embodiment, the reactant gas stream may contain at least about 99.9 vol% methane.
[0051] In an embodiment, the reactant gas stream may also contain at least about 5 vol% and no more than about 50 vol% hydrogen.
[0052] In this embodiment, the reactant gas stream may also contain carbon dioxide. The reactant gas stream may, but does not need to, be a stream of biogas or purified biogas.
[0053] In this embodiment, the temperature in step (b) can be at least about 600°C and not more than about 750°C. The temperature in step (b) can, but does not need to be, at least about 650°C and not more than about 725°C.
[0054] In this embodiment, step (b) can be performed in a suspended bed reactor.
[0055] In the embodiments, at least a portion of the elemental carbon solid may be formed on the particle surface of the catalyst composition.
[0056] While specific embodiments and applications have been described and illustrated, this disclosure is not limited to the precise configurations and components described herein. Various modifications, alterations, and variations that will be apparent to those skilled in the art may be made to the arrangement, operation, and details of the methods and systems disclosed herein without departing from the spirit and scope of the entire disclosure.
[0057] As used herein, unless otherwise stated, the terms “about,” “approximately,” etc., when used in relation to numerical limits or ranges, mean that the limit or range referenced may vary by up to 10%. As a non-limiting example, “about 750” can mean as small as 675 or as large as 825, or any value in between. When used in relation to a ratio or relationship between two or more numerical limits or ranges, the terms “about,” “approximately,” etc., mean that each limit or range may vary by up to 10%; as a non-limiting example, a statement that two quantities are “approximately equal” can mean that the ratio between the two quantities is as small as 0.9:1.1 or as large as 1.1:0.9 (or any value in between), while a statement of a four-way ratio of “about 5:3:1:1” can mean that the first number in the ratio can be any value of at least 4.5 and no more than 5.5, the second number in the ratio can be any value of at least 2.7 and no more than 3.3, and so on.
[0058] The embodiments and configurations described herein are neither complete nor exhaustive. As will be understood, other embodiments may utilize one or more of the features described above or below, individually or in combination. Detailed Implementation
[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. All patents, applications, published applications, and other publications cited herein are incorporated herein by reference in their entirety. Where a term has multiple definitions, the definition provided in the description of the invention shall prevail unless otherwise stated.
[0060] As used herein, unless otherwise stated, the term "biogas" refers to a gaseous mixture prepared by the anaerobic digestion of an organic substrate by anaerobic and / or methanogenic microorganisms, comprising at least methane and carbon dioxide. The term biogas as used herein typically (but not always) also includes hydrogen sulfide, siloxanes, or other sulfur compounds when initially prepared; unless otherwise stated, the term "purified biogas" as used herein refers to biogas that has been treated to remove at least a portion of the sulfur compounds therefrom.
[0061] Catalyst composition
[0062] This disclosure provides catalyst compositions that can be used to catalyze the decomposition of methane into solid carbon structures and hydrogen, and more specifically, to prepare highly selective and / or pure carbon solids (e.g., graphite nanofibers) and carbon monoxide-free hydrogen products having selected sizes, morphologies, and / or structures. Slightly differently, the catalyst compositions according to this disclosure provide a pathway for the large-scale (commercial-scale) preparation of specific types of carbon nanofibers, primarily or entirely composed of crystalline graphite (e.g., sheet-like carbon nanofibers, wherein the nanofibers comprise sheets aligned perpendicular to the long axis of the nanofibers), which has not been achieved to date.
[0063] The catalyst composition according to this disclosure can be made using the general chemical formula α. w Ni x β y O or α w Ni x β y γ z O represents an element of Group 13 of IUPAC (i.e., boron, aluminum, gallium, indium, and / or thallium), an element of Group 2 of IUPAC (i.e., beryllium, magnesium, calcium, strontium, and / or barium), and an element of Group 11 of IUPAC (i.e., copper, silver, and / or gold). Most typically (but not exclusively), α is composed primarily or entirely of aluminum, β is composed primarily or entirely of magnesium, and γ (when present) is composed primarily or entirely of copper. It should be clearly understood that in any composition according to this disclosure, wherein any one or more of α, β, or γ is composed of two or more elements, the corresponding stoichiometric subscripts in the general chemical formula given above indicate the total amount of the two or more elements; as a non-limiting example, in a composition represented by the formula AlNi5MgCaO, the stoichiometric subscript y equals 2 because each mole of the composition contains two moles of Group 2 elements (one mole of magnesium and one mole of calcium) as β, and in a composition represented by the formula Al2Ni8Mg4CuAgO, the stoichiometric subscript z equals 2 because each mole of the composition contains two moles of Group 11 elements (one mole of copper and one mole of silver) as γ.
[0064] In previous work, nickel-based catalysts appeared to offer the highest activity and have been the most frequently used catalysts among all catalysts studied for the catalytic decomposition of methane. Nickel, in its metallic (i.e., non-ionized) state, forms a face-centered cubic (FCC) crystal system. Without wishing to be bound by any particular theory, the inventors hypothesize that the catalyst composition of this disclosure catalyzes the decomposition of methane into solid carbon and hydrogen by chemisorbing methane gas molecules onto the (100) and / or (111) faces of the FCC nickel crystal in which the decomposition reaction occurs. Therefore, in the catalyst composition disclosed herein, it is preferred that at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, at least about 85%, at least about 90%, or at least about 95% of the active nickel sites are in a metallic state, thereby increasing the number of FCC nickel crystal faces that can be used for the chemisorption and decomposition of methane molecules.
[0065] Similarly, without wishing to be bound by any particular theory, the inventors hypothesize that one or more α elements (e.g., aluminum, etc.), one or more β elements (e.g., magnesium, etc.), and (when present) γ elements (e.g., copper, etc.) in the catalyst compositions of this disclosure act as activators, promoters, or other species that have a beneficial effect on the manufacture or use of the catalyst compositions. As a first non-limiting example, the inventors hypothesize that one or more α elements (e.g., aluminum, etc.) can at least partially control the formation and growth of solid carbon nanostructures generated by methane decomposition, and therefore, based on the teachings of this disclosure, those skilled in the art can select the desired relative amounts of one or more α elements in the composition to control, optimize, select, and / or adjust the size, morphology, and / or structure of carbon solids (e.g., nanofibers, nanotubes, etc.) with high purity and / or specificity. As a second non-limiting example, the inventors hypothesize that one or more β elements (e.g., magnesium, etc.) can stabilize FCC nickel crystals or otherwise maintain nickel in a metallic state, thereby reducing the degree of calcination required during the manufacture of the catalyst composition and / or improving the catalytic activity of the catalyst composition by increasing the proportion of active nickel sites present in the metallic state (i.e., as FCC crystals). As a third non-limiting example, the inventors hypothesize that one or more γ elements (e.g., copper, etc.) can allow the operating temperature of the methane decomposition process to be reduced by at least about 50°C when they are present; similar to nickel, stable Group 11 elements (copper, silver, and gold) form FCC crystals when in the metallic state. Therefore, in some embodiments, it is preferable that at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, at least about 85%, at least about 90%, or at least about 95% of the active sites of one or more γ elements are in the metallic state.
[0066] In many embodiments of this disclosure, α may be primarily or entirely composed of aluminum. However, it should be clearly understood that any one or more other elements from the same column of the periodic table, i.e., Group 13 of IUPAC (sometimes referred to as the "boron group"), such as boron, gallium, indium, and / or thallium, may constitute at least a portion of one or more α elements in the catalyst composition according to this disclosure, and in some embodiments, may constitute all of one or more α elements in the catalyst composition according to this disclosure. Without wishing to be bound by any particular theory, the inventors hypothesize that other Group 13 elements of IUPAC (e.g., boron, gallium, indium, and / or thallium) may function in the catalyst composition of this disclosure in the same or similar way as aluminum, for example, at least partially controlling the formation and growth of solid carbon nanostructures produced by the decomposition of methane.
[0067] In many embodiments of this disclosure, β may consist primarily or entirely of magnesium. However, it should be clearly understood that any one or more other elements from the same column of the periodic table, i.e., Group 2 (alkaline earth metals) of IUPAC, such as beryllium, calcium, strontium, and / or barium, may constitute at least a portion of one or more β elements in the catalyst composition according to this disclosure, and in some embodiments, may constitute all of one or more β elements in the catalyst composition according to this disclosure. Without wishing to be bound by any particular theory, the inventors hypothesize that other Group 2 elements of IUPAC (e.g., beryllium, calcium, strontium, and / or thallium) may function in the catalyst composition of this disclosure in the same or similar way as magnesium, for example, stabilizing FCC nickel crystals or otherwise maintaining nickel in a metallic state.
[0068] In many embodiments of this disclosure, γ (when present) may consist primarily or entirely of copper. However, it should be clearly understood that any one or more other elements from the same column of the periodic table, i.e., Group 11 of IUPAC, such as silver and / or gold, may constitute at least a portion of the γ element in the catalyst composition according to this disclosure, and in some embodiments, may constitute all of the γ element in the catalyst composition according to this disclosure. Without wishing to be bound by any particular theory, the inventors hypothesize that other Group 11 elements of IUPAC (e.g., silver and / or gold) may function in the catalyst composition of this disclosure in the same or similar way as copper, for example, allowing the operating temperature of the methane decomposition process to be reduced by at least about 50°C.
[0069] The inventors have generally found that an important parameter for controlling the type of carbon structure formed by the decomposition of methane using the catalyst composition of this disclosure is the molar ratio of one or more α elements to nickel, i.e., the general chemical formula α w Ni x β y O or α w Ni x β y γ zThe ratio of w:x in O. Most preferably, this ratio (or in other words, the number of moles of α-element atoms per mole of nickel in the catalyst composition) is at least about 0.1 and not more than about 0.5; as a non-limiting example, this ratio may be about 0.10, about 0.11, about 0.12, about 0.13, about 0.14, about 0.15, about 0.16, about 0.17, about 0.18, about 0.19, about 0.20, about 0.21, about 0.22, about 0.23, about 0.24, about 0.25, about 0.26, about 0. 0.27, about 0.28, about 0.29, about 0.30, about 0.31, about 0.32, about 0.33, about 0.34, about 0.35, about 0.36, about 0.37, about 0.38, about 0.39, about 0.40, about 0.41, about 0.42, about 0.43, about 0.44, about 0.45, about 0.46, about 0.47, about 0.48, about 0.49, or about 0.50, or alternatively, any value within any subrange of any two of these values.
[0070] The inventors have generally discovered that in methane decomposition processes utilizing catalysts, another important parameter for maximizing the catalytic activity of the catalyst composition, thereby maximizing the yield of solid carbon products and hydrogen, is the molar ratio of nickel to β element, i.e., the ratio of nickel to β element in the general chemical formula α. w Ni x β y O or α w Ni x β y γ zThe x:y ratio in O. Most preferably, this ratio (or in other words, the number of moles of nickel atoms per mole of β-element atoms in the catalyst composition) is at least about 1.0 and no more than about 6.2; as a non-limiting example, this ratio can be about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, about 3.0, about 3.1, or about 3.2. The values are approximately 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, or 6.2, or alternatively, any value within any subrange of any two of these values. Generally, without wishing to be bound by any particular theory, the inventors have found that the yields of solid carbon products and hydrogen in a catalytic methane decomposition process are sufficiently high to make the process commercially viable when the x:y ratio is in the range of approximately 1.0 to approximately 6.2. More specifically, in some embodiments, the yields of solid carbon products and hydrogen can be maximized when the x:y ratio is at least about 1.8 and no more than about 2.8, or alternatively, when the x:y ratio is about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, or any value within any subrange of any two of these values. Additionally or alternatively, in embodiments that include the γ element (i.e., the catalyst composition is composed of the general chemical formula α...), the yields of solid carbon products and hydrogen can be maximized. w Ni x β y γ z In the expression (O), the x:y ratio can preferably be at least about 1.3 and no more than about 3.6; as a non-limiting example, in the embodiments, the ratio can be about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, about 3.0, about 3.1, about 3.2, about 3.3, about 3.4, about 3.5, or about 3.6, or alternatively, it can be any value within any subrange of any two of these values.
[0071] The inventors have generally discovered that in a catalyst composition comprising the general chemical formula α w Ni x βy γ z In the embodiment indicated by O, another important parameter for further reducing the operating temperature at which methane decomposition occurs is the molar ratio of nickel to γ element, i.e., the ratio of the general chemical formula α. w Ni x β y γ z The x:z ratio in O. Most preferably, this ratio (or in other words, the number of moles of nickel atoms per mole of γ-element atoms in the catalyst composition) is at least about 1.0 and not more than about 19.0; as a non-limiting example, this ratio can be about 1.0, about 1.5, about 2.0, about 2.5, about 3.0, about 3.5, about 4.0, about 4.5, about 5.0, about 5.5, about 6.0, about 6.5, about 7.0, about 7.5, about 8.0, about 8.5, or about 9. 0, about 9.5, about 10.0, about 10.5, about 11.0, about 11.5, about 12.0, about 12.5, about 13.0, about 13.5, about 14.0, about 14.5, about 15.0, about 15.5, about 16.0, about 16.5, about 17.0, about 17.5, about 18.0, about 18.5, or about 19.0, or alternatively, any value within any subrange of any two of these values. Generally, without wishing to be bound by any particular theory, the inventors have found that when the x:z ratio is in the range of about 1.0 to about 19.0, the operating temperature required to induce methane decomposition can be reduced by at least about 50°C. More specifically, in some embodiments, the x:z ratio is at least about 2.3 and no more than about 9.0, or alternatively, the ratio is about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, about 3.0, about 3.1, about 3.2, about 3.3, about 3.4, about 3.5, about 3.6, about 3.7, about 3.8, about 3.9, about 4.0, about 4.1, about 4.2, about 4.3, about 4.4, about 4.5, about 4.6, about 4.7, about 4.8, about 4.9, about 5.0, about 5.1, about 5.2, about 5.3, about 5.4, about 5.5, or about 5. 6. Approximately 5.7, approximately 5.8, approximately 5.9, approximately 6.0, approximately 6.1, approximately 6.2, approximately 6.3, approximately 6.4, approximately 6.5, approximately 6.6, approximately 6.7, approximately 6.8, approximately 6.9, approximately 7.0, approximately 7.1, approximately 7.2, approximately 7.3, approximately 7.4, approximately 7.5, approximately 7.6, approximately 7.7, approximately 7.8, approximately 7.9, approximately 8.0, approximately 8.1, approximately 8.2, approximately 8.3, approximately 8.4, approximately 8.5, approximately 8.6, approximately 8.7, approximately 8.8, approximately 8.9, or approximately 9.0, or alternatively, any value within any subrange of any two of these values, can optimize the operating temperature.
[0072] Parameters related to the chemical composition and physical structure of a catalyst can be controlled, designed, optimized, selected, and / or adjusted to provide the desired characteristics of a methane decomposition process in which a catalyst composition is used, as described in more detail in this disclosure. An important parameter of the catalyst composition suitable for the methods and systems of this disclosure is the effective surface area of the catalyst, i.e., the total surface area of the catalyst that is in direct contact with or can be in direct contact with methane. The total surface area of solid catalyst particles has a significant impact on the reaction rate; generally, for a given mass of catalyst, the smaller the catalyst particle size, the larger the effective surface area.
[0073] Another important parameter of the catalyst composition applicable to the methods and systems of this disclosure is the diffusion profile of the catalyst composition. In turn, the diffusion profile is generally controlled by the total porosity and pore size of the catalyst particles themselves, which determines the extent to which reactant molecules (i.e., methane molecules) can diffuse into and through the catalyst particles. In the embodiments, the pore size range of the catalyst particles can be from as small as approximately [missing information - likely a number]. (0.4 nm) to approximately 1,500 μm, or alternatively, in areas with The lower bound of any integer angstrom up to 1,500 μm and Any range of any integer upper limit up to 1,500 μm angstrom.
[0074] In view of the above considerations, those skilled in the art can select and optimize suitable materials and geometries for the catalyst composition. In view of this disclosure, those skilled in the art understand that the motivation for such selection is the desired kinetics of the methane decomposition reaction.
[0075] Method for preparing catalyst compositions
[0076] One aspect of this disclosure is a method for preparing a catalyst composition for a methane decomposition process. An advantage and benefit of the catalyst compositions of this disclosure is that they can be manufactured relatively easily, inexpensively, and rapidly using readily available reactants. In embodiments of this disclosure, the method for preparing the catalyst compositions disclosed herein involves first providing a solution or slurry of hydroxides of one or more β elements; as a non-limiting example, when β is magnesium, magnesium hydroxide slurry is widely available in large quantities due to its extensive use in municipal and industrial wastewater treatment systems. Subsequently, salts of other non-oxygen elements of the catalyst composition, namely nickel, one or more α elements (e.g., aluminum), and in some embodiments, one or more γ elements (e.g., copper), can be added to, mixed with, or dissolved in the slurry in volume / solid form or in a suitable solvent solution (as will be understood and known to those skilled in the art); suitable salts include chlorides, nitrates, and sulfates of the desired elements, and in many embodiments, the most preferred salts are those from which anions readily evaporate upon subsequent heating (e.g., aluminum chloride). Therefore, in a non-limiting exemplary embodiment, salts of nickel (e.g., nickel chloride and / or nickel nitrate), aluminum (e.g., aluminum sulfate and / or aluminum chloride), and copper (e.g., copper chloride and / or copper nitrate) are mixed into a magnesium hydroxide slurry to form a catalyst precursor. As those skilled in the art will understand, the relative stoichiometric amounts of the nickel, α, β, and (when present) γ salts can be readily selected at this stage to provide an appropriate ratio among any two or more of w, x, y, and z in the finished catalyst composition. The catalyst precursor solution, slurry, and / or mixture is then calcined in a suitable environment (e.g., air, hydrogen, nitrogen, argon, sulfur dioxide, nitrogen oxides, nitrogen dioxide, or combinations thereof) at a suitable temperature (in some embodiments, between about 500°C and about 1,000°C, typically between about 600°C and about 900°C, more typically between about 750°C and about 850°C) for a period of time (in some embodiments, between about 1 hour and about 30 hours, most typically about 24 hours) sufficient to evaporate substantially all present anions and convert at least a portion of nickel, and in some embodiments, to convert at least a portion of any one or more of α, β, and (if present) γ elements to a metallic state, as described in other parts of this disclosure.After calcination, the metals in the catalyst composition readily oxidize when exposed to air; therefore, as a final step, the calcined product is reduced for a period of time at a suitable temperature (typically between about 600°C and about 1,000°C, most typically between about 850°C and about 950°C) in a reducing atmosphere (typically hydrogen, or a mixture of hydrogen and an inert gas, such as argon) sufficient to cause nickel, one or more α elements, one or more β elements, and (when present) one or more γ elements to merge into a single phase and form a single phase of the general chemical formula α. w Ni x β y O or α w Ni x β y γ z The composition is represented by O. In some embodiments, the reducing environment includes hydrogen gas, at least a portion of which can be recovered from a downstream processing unit, in which a previously prepared catalyst composition is used to decompose methane into solid carbon products and a stream of hydrogen gas free of carbon monoxide.
[0077] Methods for catalytic methane decomposition
[0078] Another aspect of this disclosure is a method for preparing solid carbon products (particularly, in many embodiments, solid carbon products of high selectivity / purity having defined or selected sizes, morphologies, and / or structures, such as carbon nanofibers or nanotubes) and hydrogen gas (particularly, in many embodiments, a hydrogen gas stream free of carbon monoxide) by catalytic decomposition of methane using the catalyst composition disclosed herein. In embodiments of this method, a catalyst of the general chemical formula α is provided. w Ni x β y O or α w Ni x β y γ z The catalyst composition is represented by O. The catalyst composition is then contacted with methane gas, causing at least a portion of the methane gas to decompose into solid carbon products and hydrogen. In some embodiments, the solid carbon products may be formed upon direct contact with particles of the catalyst composition (e.g., growth on the surface of the particles of the catalyst composition). In some embodiments, at least a portion of one or both of the solid carbon products and hydrogen may further react to form a product of downstream interest; additionally or alternatively, as described above, at least a portion of the hydrogen may be recovered as a component of the reducing atmosphere for synthesizing the catalyst composition.
[0079] Most typically, methane used in the methods according to this disclosure can be provided as a component of the natural gas stream, but it should be clearly understood that the methane can be derived from any natural or artificial source of methane. The methane gas stream may contain one or more other gases, such as hydrogen, carbon dioxide, nitrogen dioxide, nitrogen oxides, water, or other hydrocarbons (e.g., ethane, propane, butane, etc.); in some embodiments, the methane stream may be a biogas stream or a purified biogas stream. The catalyst composition selectively decomposes methane and does not react with other gases in the gas stream.
[0080] The methods for catalytic decomposition of methane according to this disclosure are carried out at temperatures from about 500°C to about 800°C, typically between about 600°C and 750°C, and more typically between about 650°C and about 725°C; these operating temperatures are significantly lower than the temperatures required for the pure thermal decomposition of methane (about 1,400°C), and therefore they have the advantage of a significantly reduced energy input. The catalytic methane decomposition methods of this disclosure can be carried out at operating pressures between about 0.05 kPa and about 500 kPa, ranging from ambient and / or atmospheric pressure; in some embodiments, these operating pressures may be total (absolute) pressures, while in other embodiments, they may be the partial pressures of methane present in a gas stream (wherein the gas stream contains gases other than methane). Generally, the catalyst composition is provided in an unstructured form (i.e., as a “bulk” or “free” material not attached to any structure or substrate). Methane decomposition can be carried out in any suitable type of reactor, including, but not limited to, a slurry bed reactor, in which a methane gas stream flows through and / or through a slurry bed of catalyst.
[0081] One advantage of the catalytic methane decomposition methods according to this disclosure is that they can be used for greenhouse gas capture and / or reduction of greenhouse gas emissions. In particular, given the high cost and / or safety or purity issues associated with previous methods for capturing or reducing methane emissions and subsequently decomposing methane into carbon solids and hydrogen (e.g., the presence of carbon monoxide or other hazardous substances in the hydrogen stream and / or poor control over the resulting carbon solid structure), the methane decomposition methods of this disclosure provide high-value, high-purity products with fewer safety and toxicity issues, namely the desired highly specific / pure solid carbon structure and a carbon monoxide-free hydrogen stream. Therefore, the catalytic decomposition methods disclosed herein represent a more economically and environmentally attractive pathway for capturing, reducing, and / or mitigating methane emissions compared to those previously known in the art.
[0082] The invention is further described by way of the following non-limiting examples.
[0083] Example 1:
[0084] Effect of catalyst composition on the yield and morphology of carbon nanofibers
[0085] A precatalyst calcination product was prepared by combining chloride and / or nitrate salts of aluminum, nickel, and magnesium to form a precursor mixture, and then calcining the precursor mixture in air at 500°C. For each of several experimental runs, relative amounts of nickel and magnesium salts were selected to provide different molar ratios of nickel to magnesium (i.e., the desired x:y ratio) in the precatalyst calcination product, thereby providing different molar ratios of nickel to magnesium (i.e., the desired x:y ratio) in the finished catalyst composition.
[0086] For each run of the experiment, one of the pre-catalyst calcined products prepared therefrom was placed in a quartz flow reactor heated by a Lindberg horizontal tube furnace; specifically, 50 mg of the powdered calcined sample was placed in a ceramic "sponge" made of alumina fibers at the center of the reactor tube in the furnace. The system was flushed with argon for 30 minutes, and then the final Al was produced by reducing the calcined product at 850 °C in an atmosphere of 10 vol% H2 / 90 vol% argon. w Ni x Mg y The catalyst was purged with argon again. Methane was then introduced into the reactor, and the reaction was allowed to occur in the presence of an operating temperature of 550–750 °C and ambient (atmospheric) pressure. The flow rate of the methane gas (60 mL / min) was precisely monitored and regulated using an MKS mass flow controller, allowing for the maintenance of a constant composition of the feed gas. The hot feed gas thus flowed through an alumina “sponge” and “lifted” the catalyst to a fluidized state. The progress of the reaction was monitored by sampling the inlet and outlet gases at regular intervals and analyzing the reactants and products by gas chromatography; the flow of methane and the operating temperature of 550–750 °C were maintained until complete catalyst deactivation was observed (i.e., gas chromatography showed no H2 in the outlet gas). The reaction resulted in the deposition of carbon solids, the yield of which was determined by gravimetric analysis after the system cooled to room temperature. The solid carbon products were also examined to determine the proportion (by mass) of solids prepared as sheet-like nanofibers (a particularly desirable type of carbon nanostructure). Table 1 shows the nickel / magnesium molar ratio (i.e., the general chemical formula Al) for each experimental run. w Ni x Mg y The x:y ratio in O), the yield of solid carbon (per mass of pre-reduced calcined product), the yield of hydrogen (per mass of pre-reduced calcined product), and the proportion of solid carbon prepared as sheet nanofibers.
[0087] Table 1
[0088]
[0089] Example 2:
[0090] Effect of reduction temperature on catalyst performance
[0091] Repeat the steps of Example 1, except that the x:y ratio is kept constant at 2.4 and the temperature of the hydrogen / argon reduction step is varied between 600 °C and 1,000 °C. Maintain the flow of methane and the reactor temperature between 550 and 750 °C until the methane conversion (measured by gas chromatography of the outlet gas) decreases to less than 4%. The catalyst was also examined by X-ray crystallography to determine its metal (i.e., non-ionized or Ni) state. 0 The proportion of nickel atoms in the ) state. Table 2 shows the reduction temperature, percentage of converted methane (after 1 hour), catalyst lifetime, yield of hydrogen and solid carbon (per mass of pre-reduction calcined product), and proportion of carbon solid prepared as sheet nanofibers for each experimental run.
[0092] Table 2
[0093]
[0094] In the absence of any element not specifically disclosed herein, the concepts disclosed illustratively herein may be appropriately practiced. However, it will be apparent to those skilled in the art that many changes, variations, modifications, other uses, and applications of this disclosure are possible, and such changes, variations, modifications, other uses, and applications without departing from the spirit and scope of this disclosure are deemed to be covered by this disclosure.
[0095] The foregoing discussion is for illustrative and descriptive purposes only. It is not intended to limit this disclosure to the one or more forms disclosed herein. For example, in the foregoing detailed description, various features are combined in one or more embodiments for the purpose of simplifying this disclosure. Features of embodiments may be combined in alternative embodiments other than those described above. This approach of the disclosure should not be construed as reflecting an intention to claim more features than expressly referenced in each claim. Rather, as reflected in the following claims, the inventive aspect exists in fewer than all features of a single foregoingly disclosed embodiment. Therefore, the following claims are incorporated herein by reference, each claim being a separate embodiment.
[0096] Furthermore, while this disclosure includes descriptions of one or more embodiments and certain variations and modifications, other variations, combinations, and modifications are within the scope of this disclosure and may fall within the skill and knowledge of those skilled in the art upon understanding this disclosure. It is intended to obtain rights, including alternative embodiments and claimed alternative, interchangeable, and / or equivalent structures, functions, scopes, or steps, to the permissible extent, whether such alternative, interchangeable, and / or equivalent structures, functions, scopes, or steps are disclosed herein, and is not intended to disclose any patentable subject matter.
Claims
1. A catalyst composition represented by the general formula Al w Ni x Mg y O wherein: The ratio of w to x is at least 0.1 and no more than 0.
5. The x:y ratio is at least 1.0 and no more than 6.2, and At least 25% of the active nickel sites in the catalyst composition are in a metallic state.
2. The catalyst composition according to claim 1, wherein the x:y ratio is at least 1.8 and not more than 2.
8.
3. The catalyst composition according to claim 1, wherein at least 50% of the active nickel sites in the catalyst composition are in a metallic state.
4. A catalyst composition represented by the general formula Al w Ni x Mg y γ z O wherein: γ is at least one element selected from the group consisting of copper (Cu), silver (Ag), gold (Au), and combinations thereof. The ratio of w to x is at least 0.1 and no more than 0.
5. The ratio of x to y is at least 1.3 and no more than 3.
6. The x:z ratio is at least 1.0 and no more than 19.0, and At least 25% of the active nickel sites in the catalyst composition are in a metallic state.
5. The catalyst composition according to claim 4, wherein γ is copper (Cu).
6. The catalyst composition according to claim 4, wherein the x:y ratio is at least 1.8 and not more than 2.
8.
7. The catalyst composition according to claim 4, wherein the x:z ratio is at least 2.3 and not more than 9.
0.
8. The catalyst composition according to claim 4, wherein at least 50% of the active nickel sites in the catalyst composition are in a metallic state.
9. The catalyst composition according to claim 4, wherein at least 25% of the active sites of one or more γ elements in the catalyst composition are in a metallic state.
10. The catalyst composition according to claim 9, wherein at least 50% of the active sites of one or more γ elements in the catalyst composition are in a metallic state.
11. A method for manufacturing a catalyst composition, comprising: (a) A catalyst precursor composition is provided, comprising w parts by mole of aluminum (Al), x parts by mole of nickel, and y parts by mole of magnesium (Mg), wherein: The ratio of w:x is at least 0.1 and no more than 0.5; and The x:y ratio is at least 1.0 and no more than 6.2; (b) Calcining the catalyst precursor composition at a temperature of at least 500°C and not exceeding 1,000°C to form the calcined product; and (c) The calcined product is reduced at a temperature of at least 600°C and not exceeding 1,000°C in an atmosphere containing hydrogen to form a catalyst composition.
12. The method of claim 11, wherein the ratio of x:y is at least 1.8 and no more than 2.
8.
13. The method according to claim 11, wherein, After step (c), at least 50% of the active nickel sites in the catalyst composition are in a metallic state.
14. The method of claim 11, wherein: The catalyst precursor composition also includes one or more γ elements in molar amounts, wherein the one or more γ elements are selected from the group consisting of copper (Cu), silver (Ag) and gold (Au); The ratio of x:y is at least 1.3 and no more than 3.6; and The x:z ratio is at least 1.0 and no more than 19.
0.
15. The method of claim 14, wherein one or more γ elements comprise copper (Cu).
16. The method of claim 15, wherein one or more γ elements are composed of copper (Cu).
17. The method of claim 14, wherein the x:z ratio is at least 2.3 and no more than 9.
0.
18. The method according to claim 14, wherein, After step (c), at least 25% of the active sites of one or more γ elements in the catalyst composition are in a metallic state.
19. The method according to claim 18, wherein, After step (c), at least 50% of the active sites of one or more γ elements in the catalyst composition are in a metallic state.
20. The method of claim 11, wherein the temperature in step (b) is at least 600°C and not more than 900°C.
21. The method of claim 20, wherein the temperature in step (b) is at least 750°C and not more than 850°C.
22. The method of claim 11, wherein the atmosphere in step (c) further comprises argon.
23. The method of claim 11, wherein the temperature in step (c) is at least 850°C and not more than 950°C.
24. A method for the catalytic decomposition of methane to prepare elemental carbon solid and a product stream containing hydrogen, comprising: (a) Provided by Al w Ni x Mg y O or Al w Ni x Mg y γ z O represents the catalyst composition, wherein: γ is at least one element selected from the group consisting of copper (Cu), silver (Ag), gold (Au), and combinations thereof. The ratio of w to x is at least 0.1 and no more than 0.
5. The x:y ratio is at least 1.0 and no more than 6.2; When γ exists, the x:z ratio is at least 1.0 and no more than 19.0, and At least 25% of the active nickel sites in the catalyst composition are in the metallic state; and (b) The catalyst composition is contacted with a reactant gas stream containing methane gas at a temperature of at least 500°C and not exceeding 800°C.
25. The method of claim 24, wherein γ is copper (Cu).
26. The method of claim 24, wherein the ratio of x:y is at least 1.8 and no more than 2.
8.
27. The method of claim 24, wherein when γ is present, the x:z ratio is at least 2.3 and no more than 9.
0.
28. The method of claim 24, wherein at least 50% of the active nickel sites in the catalyst composition are in a metallic state.
29. The method of claim 24, wherein at least 25% of the active sites of one or more γ elements in the catalyst composition are in a metallic state.
30. The method of claim 29, wherein at least 50% of the active sites of one or more γ elements in the catalyst composition are in a metallic state.
31. The method of claim 24, wherein at least 85% by weight of the carbon solids are formed as graphite nanofibers, the graphite nanofibers comprising sheets perpendicularly aligned to the fiber axis.
32. The method of claim 24, wherein the product stream is free of carbon monoxide.
33. The method of claim 24, wherein the reactant gas stream comprises at least 99.9 vol% methane.
34. The method of claim 24, wherein the reactant gas stream further comprises at least 5 vol% and no more than 50 vol% hydrogen.
35. The method of claim 24, wherein the reactant gas stream further comprises carbon dioxide.
36. The method of claim 35, wherein the reactant gas stream is a biogas stream.
37. The method of claim 24, wherein the temperature in step (b) is at least 600°C and not more than 750°C.
38. The method of claim 37, wherein the temperature in step (b) is at least 650°C and not more than 725°C.
39. The method of claim 24, wherein step (b) is performed in a slurry bed reactor.
40. The method of claim 24, wherein at least a portion of the elemental carbon solid may be formed on the particle surface of the catalyst composition.
Citation Information
Patent Citations
Catalyst for the generation of CO-free hydrogen from methane
US6995115B2
CO-free hydrogen from decomposition of methane
US7001586B2
Metal supported silica based catalytic membrane reactor assembly
CN103596671A
Platinum and rhodium and / or iron containing catalyst formulations for hydrogen generation
CN1729051A
